Transcatheter arterial infusion chemotherapy with cisplatin in combination with transcatheter arterial chemoembolization decreases intrahepatic distant recurrence of unresectable hepatocellular carcinoma - Naoto Kawabe (JGH Open, 2021)
Abstract Background and Aim This study investigated the efficacy of transcatheter arterial infusion (TAI) chemotherapy with cisplatin combined with transcatheter arterial chemoembolization (TACE). The goal was to prevent intrahepatic distant recurrence (IDR) of hepatocellular carcinoma (HCC), compared with TACE alone, in patients with unresectable HCC. Methods We conducted a historical cohort study, which involved 68 unresectable HCC patients. The study was performed on 44 and 24 consecutive patients who underwent TAI using cisplatin combined with TACE using epirubicin and TACE using epirubicin alone, respectively. We performed a propensity score analysis to identify the independent risk factors associated with IDR, and constructed propensity score‐adjusted survival curves. Results After propensity score‐adjusting, the adjusted cumulative IDR rates at 1 and 3 years were 76.8 and 76.8% in TACE alone group, and 21.3 and 73.1% in TACE with TAI group, respectively. TACE alone group had a significantly higher IDR rate in comparison with TACE with TAI group (P = 0.0073). Combined with TAI was associated with preventing IDR after propensity score‐adjusting (hazard ratio [HR] 0.40, 95% confidence intervals [CI] 0.17–0.91, P = 0.028). Combined with TAI (HR 0.26, 95% CI 0.10–0.68, P = 0.0056) and Stage ≥III (HR 2.98, 95% CI 1.25–7.12, P = 0.014) were independent IDR predictors after adjusting for significant risk factors with propensity score. Conclusions We demonstrated that cisplatin TAI accompanied with TACE decreased IDR compared with TACE alone. Our findings suggest that cisplatin TAI might contribute to a longer progression‐free period in unresectable HCC patients treated with TACE.